2017
DOI: 10.1016/j.bj.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage biology plays a central role during ionizing radiation-elicited tumor response

Abstract: Radiation therapy is one of the major therapeutic modalities for most solid tumors. The anti-tumor effect of radiation therapy consists of the direct tumor cell killing, as well as the modulation of tumor microenvironment and the activation of immune response against tumors. Radiation therapy has been shown to promote immunogenic cells death, activate dendritic cells and enhance tumor antigen presentation and anti-tumor T cell activation. Radiation therapy also programs innate immune cells such as macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 106 publications
4
61
0
Order By: Relevance
“…30 Iba1 is a microglia/macrophage-specific calcium-binding protein, which facilitates cell migration and phagocytosis by microglia. 31 Previous studies have shown that RT has a strong impact on tissue microenvironments 25,32 In conclusion, our study provides novel and comprehensive insights into the benefits of dual treatment, including radiosensitizing PCa tumor tissues to RT and radioprotecting normal pelvic organs from RT. The underlying processes are complicated and involve crosstalk between the epithelial, fibroblasts, endothelial, and immune cells as well as soluble paracrine and autocrine factors including cytokines, chemokines, growth factors, and proteases.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…30 Iba1 is a microglia/macrophage-specific calcium-binding protein, which facilitates cell migration and phagocytosis by microglia. 31 Previous studies have shown that RT has a strong impact on tissue microenvironments 25,32 In conclusion, our study provides novel and comprehensive insights into the benefits of dual treatment, including radiosensitizing PCa tumor tissues to RT and radioprotecting normal pelvic organs from RT. The underlying processes are complicated and involve crosstalk between the epithelial, fibroblasts, endothelial, and immune cells as well as soluble paracrine and autocrine factors including cytokines, chemokines, growth factors, and proteases.…”
Section: Discussionmentioning
confidence: 73%
“…Tumor responses to RT and clinical outcomes depend on the intrinsic repair capacity, oxygenation of the tumor tissue, modulation of the tumor microenvironment, and the activation of the immune response, as well as other factors . Several pharmacological strategies have been exploited to develop effective and minimally‐toxic radiosensitizers including small molecules, macromolecules, and nanomaterials .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that progression of PD can be mitigated and in some instances reversed via neuroprotective agents (e.g., donepezil; rosiglitazone) that exert hormetic dose‐responses to induce microglia to express and sustain the anti‐inflammatory M2 phenotype (Chen, Hou, Xu, & Wu, ; Pisanu et al, ). Moreover, hormetic bi‐phasic dose‐responses may be involved in the process of macrophage reprogramming and polarization that is produced by chemicals, as well as ionizing radiation (Genard, Lucas & Michiels, ; Walton, ; Wu et al, ). Other studies have shown that preconditioning‐induced protection responses are associated with increased M2 polarization across multiple organs/cell types (e.g., bone, Young et al, ; spinal cord, Hayakawa et al, ; mesenchymal stem cells, Lin et al, , Mountziaris, Tzouanas, & Mikos, ; Kidney, Hato et al, ) reflecting the generality of the adaptive strategy.…”
Section: Discussionmentioning
confidence: 99%